A Portrait of an EFL Learners' Explanation Text: Cohesion and Coherence - Aldha Williyan (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2020)
This study aims to explore cohesion and coherence in an explanation text written by an EFL learner. To do this, the cohesive devices of the explanation text are analyzed. Also, the text is analyzed using the Thematic progressions theory to find out the logical relationship of the sentences and whether or not the text can meet the readers’ expectations. There are several steps to analyze both elements. The first is broking up the paragraphs of the text into sentences. The second is using Thematic progressions to analyze the text. Finally, the writer analyzed the cohesive devices which function to connect sentences. All those data later are elaborated in paragraphs as descriptive-qualitative research design is employed in this study. The results shows that, in term of cohesive devices, the writer uses direct repetition, partial repetition, and same lexical set to build lexical cohesion. It is also found that the writer uses reference, substitution, and ellipsis to build grammatical cohesion. However, the writer seems to have insufficient knowledge to use the cohesive devises correctly. Additionally, the analysis of Thematic progressions shows that some sentences in the text have no logical relationship. Lastly, this study finds that the writer also seem to have insufficient knowledge of schematic structures of the explanation text. Keywords: Exposition text; Cohesive Devices; Thematic Progression